The role of literacy to reduce poverty in Islamic education - Ahmad Amin; Muhammad Adli Musa (Penerbit Universiti Kebangsaan Malaysia, 2022)
Literacy skills pave the way to gaining knowledge, and it is a vital component of every nation's development. Education is a powerful tool for eliminating poverty, increasing shared wealth, and forming a community that can deal with difficult times. The importance of education in Islam is a key part of achieving the Islamic vision of development and a prosperous way of life, which is called socio-economic development. This research attempts to investigate that Islamic education has played an important role in enhancing literacy, and it lays the foundation for reducing poverty and encouraging economic progress. The method adopted in this study was a qualitative approach starting with document analysis of the connection between literacy and poverty and the role of Islamic education in reducing poverty. The findings of this study indicate that, from the Islamic point of view, literacy is part of a broader conversation on the strategies, programs, and policies that inform a comprehensive and effective poverty reduction strategy. From the beginning of Islam, it has offered believers a chance for equality and respect regardless of whether they are poor, slaves, or without position or prestige in society. Islam holds knowledge, education, literacy, and intellectual pursuits in high regard.